The Use of Social Media for Political Socialization in Nepal: An Effectiveness Analysis of Platforms - Bhattarai, Pramila (The Outlook: Journal of English Studies, 2023)
The recent advancement of information technology has led to the advent of social media. The outburst of such social networking sites has created opportunities for several human activities, including those related to politics throughout the world; Nepal is no exception to it. Since social media is explosively increasing for political socialization in Nepal in recent times, it is now required to find its usefulness and effectiveness. In this regard, this paper attempts to explore the effectiveness of various social media platforms used for political socialization in Nepal. The study adopts an exploratory research design, using survey questionnaires for data collection. Pokhara Metropolitan City in Gandaki Province, Nepal is taken as the sample study area and the information is received from 160 respondents who are liable to cast vote in the election. The study finds a remarkable impact of social media on political socialization. The results of the study suggest that online political activities are strongly correlated to political awareness and offline political socialization. The study is expected to be useful for political parties, political leaders, political activists and the general public to determine effective social media platforms as per their usefulness for political communication in Nepal.